2016
DOI: 10.1039/c6cs00343e
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin two-dimensional layered metal hydroxides: an emerging platform for advanced catalysis, energy conversion and storage

Abstract: The unique properties of graphene are triggering a great deal of attention toward the family of ultrathin two-dimensional (2D) structures. Ultrathin layered metal hydroxides (LMHs) are increasingly being recognized as an important category in 2D nanomaterials, and the corresponding research has been experiencing a significant renaissance. Due to the flexible tunability of metal ions, their naturally positively charged plane and 2D anisotropy with nanometre thickness, ultrathin LMHs and their derived hybrids ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
257
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(258 citation statements)
references
References 50 publications
0
257
0
1
Order By: Relevance
“…In this case, a wider operating voltage can be achieved, which leads to a higher energy density [12,13]. interest because of the high redox reaction activity, relatively low cost, and environmentally friendly features [14][15][16]. It has been reported that the electrical double-layer and Faradaic reactions can be simultaneously achieved in the abundant slabs or electrochemical active sites of the LDH structure.…”
Section: Introductionmentioning
confidence: 94%
“…In this case, a wider operating voltage can be achieved, which leads to a higher energy density [12,13]. interest because of the high redox reaction activity, relatively low cost, and environmentally friendly features [14][15][16]. It has been reported that the electrical double-layer and Faradaic reactions can be simultaneously achieved in the abundant slabs or electrochemical active sites of the LDH structure.…”
Section: Introductionmentioning
confidence: 94%
“…gases and vapors such as nitrogen oxides, acetone, and ethanol [10]. 2D layered materials have been also used as precursors for obtaining thin two-dimensional metal oxides [11][12][13].…”
Section: Factors Influencing the Gas Sensing Characteristics Of Thin mentioning
confidence: 99%
“…LDHs structure exhibits a pathway facilitating carrier diffusion/transportation, therefore they received considerable attention for direct potential applications in gas sensors for monitoring a wide class of gases and vapors such as nitrogen oxides, acetone, and ethanol [10]. 2D layered materials have been also used as precursors for obtaining thin two-dimensional metal oxides [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 7, almost complete dye degradation can be achieved within 320 min, 140 min, and 5 min for RB, MB, and CV, respectively. Their degradation products have been detected and identified as non-or less-toxic anions such as SO 4 2− , NO hydro-desulfurization (HDS) processes employed for the removal of DBT, 4,6-DMDBT and BT etc. are quite challenging.…”
Section: Oxidation Catalystmentioning
confidence: 99%